(untitled) (Medical Forum Monthly, 2022)
Objective: To investigate the long-term effects of surgical thrombectomy of iliofemoral deep vein thrombosis (DVT) with regards to the occurrence of post-thrombotic syndrome (PTS) and post-surgery venous hemodynamics concerning venous insufficiency and venous obstruction. Study Design: A retrospective observational study Place and Duration of Study: This study was conducted at the surgical department of Doctors Hospital & Medical Centre Lahore from May 2019 to May 2021 for a period of 02 years. Materials and Methods: A total of 50 patients who underwent surgical thrombectomy were included in the study. Among these patients, 35 patients were diagnosed with iliofemoral DVT. 20 patients were evaluated after an average follow-up of 2 years by a comprehensive duplex mapping. CEAP and Villalta scale was used to assess and test the severity of PTS. Digital photoplethysmography (PPG) and venous occlusion plethysmography (VOP) were used to calculate venous hemodynamics. Results: After the 2-year follow-up, the primary patency rate of the iliofemoral venous segment was 85%. Venous reflux was observed in 45% of patients in the study. 55% of patients were diagnosed with mild or moderate post-thrombotic syndrome. However, no patient developed severe PTS or active ulceration. The average venous flow volume in the operated femoral was 63.2ml/100ml per minute which was notably less than controlled contralateral legs without surgery (p<0.05). The average venous refilling time (VRT) was 15.5 seconds which was significantly more than that of non-operative legs (p<0.05). Conclusion: The results of the study indicate good long-term results and excellent patency rates after surgical thrombectomy of iliofemoral veins.